Student Movement in The Era of The Joko Widodo: A New Generation of Indonesian Democracy - Sukma Aditya Ramadhan; Dinda Elysia Azhar; M. Faris Zulfauzi; Noprisyal Ramadhan; Helda Suartina; Yusuf Fadli (Universitas of Muhammadiyah Makassar, 2022)
The student movement is part of a social movement and is the most important factor in realizing social change. The democracy index in the era of Joko Widodo's administration shows a downward trend, this encourages the increase in the Indonesian student movement. Several policies of the Joko Widodo government are seen as Contrary to the interests of the community, such as the revision of the KPK Law, the drafting of the omnibus law, and the arrest of activists of civil society movements. This article explains specifically the student movements that existed during the Jokowi presidency during the first period and the second period. The research data obtained were analyzed and interpreted to see the extent to which the student movement had an impact on government policy. In the era of Jokowi's leadership, the student movement continues to oversee the government's agenda through controversial policies. In the second period under Jokowi's leadership, the student movement was still carried out and never stopped taking action as a result of several government policies that were not in favor of the community.